The SAGE handbook of economic geography - Leyshon, Andrew (Thousand Oaks, Calif. SAGE, 2011)
This companion illustrates the significance of thinking the 'economy' and the 'economic' geographically. It identifies significant stages in the discipline's development, and focuses on the key themes and ideas that inform present thinking in economic geography.
Includes bibliographical references and index.
Keywords: Economic geography; Electronic books